The Influence of Tourist Attraction, Facilities, and Social Media Promotion on Muslim Tourists’ Revisit Intention at Pancer Door Floating Mosque, Pacitan - Sandhi Agung Pratama; Happy Agustiani (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the influence of tourist attractions, facilities, and social media promotion on Muslim tourists’ revisit intention at Pancer Door Floating Mosque Pacitan. This research used a quantitative descriptive approach with primary data collected through questionnaires distributed to Muslim tourists. The sampling technique used purposive sampling with criteria including Muslim tourists aged at least 18 years and having visited Pancer Door Floating Mosque Pacitan. Data analysis was conducted using SPSS through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that tourist attractions, facilities, and social media promotion had a positive and significant effect on revisit intention. Tourist attractions in the form of religious tourism concepts combined with coastal panoramas were able to create positive experiences for visitors. Adequate facilities also increased tourist comfort and satisfaction during their visit. In addition, social media promotion played an important role in improving destination image and attracting tourists to revisit the destination. Simultaneously, tourist attractions, facilities, and social media promotion significantly influenced Muslim tourists’ revisit intention at Pancer Door Floating Mosque Pacitan.